Case of Rapid Progression of Hemiatrophy on the Face: A New Clinical Entity? - Hisashi Nomura; Shohei Egami; Tomoaki Yokoyama; Makoto Sugiura (Case Reports in Dermatological Medicine)
A lot of diseases, including lupus profundus, morphea, lipodystrophy, and Parry-Romberg syndrome, may manifest progressive hemifacial atrophy. These diseases usually progress slowly and rapid progression of atrophy is extremely rare. We report a case of elderly-onset rapid progression of hemifacial atrophy only in three weeks. Our case did not meet variable differential diagnoses. We discuss the clinical character of the patient against the past of literature and suppose it may be a new clinical entity.